Popularitas Thrifting dan Faktor Harga Terhadap Pola Konsumsi Fashion Generasi Z di Denpasar - Ni Kadek Dilla Nirmala Adinda Putri; Ni Putu Bayu Widhi Antari; I Gusti Ngurah Widya Hadi Saputra; I Made Suidarma (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the influence of thrifting popularity and price factors on fashion consumption patterns among Generation Z in Denpasar City. The rapid development of the fashion industry and the widespread use of social media have significantly influenced consumer behavior, particularly among young people. Thrifting has emerged as an alternative consumption practice due to its affordability, uniqueness, and sustainability value. This study employs a qualitative approach using observation, in-depth interviews, and documentation involving 11 informants selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results show that social media plays a significant role in increasing the popularity of thrifting, which in turn influences the preferences and purchasing decisions of Generation Z. Price is identified as the main factor driving the shift from new fashion products to second-hand items. Additionally, the study reveals a shift toward more economical, trend-oriented, and environmentally conscious consumption patterns. Thus, thrifting reflects not only a trend but also a transformation in lifestyle and consumption behavior among Generation Z.